1999
DOI: 10.1038/sj.bjc.6690533
|View full text |Cite
|
Sign up to set email alerts
|

A phase I/II study of combined weekly systemic cisplatin and locoregional hyperthermia in patients with previously irradiated recurrent carcinoma of the uterine cervix

Abstract: SummaryWe investigated the feasibility and the anti-tumour activity of weekly cisplatin and the simultaneous application of local hyperthermia in patients with a pelvic recurrence of cervical cancer in previously irradiated area. Dose levels of cisplatin 60 mg m -2 , 70 mg m -2 and 80 mg m -2 were studied. Treatment objective of hyperthermia was the achievement of a tumour temperature of ≥ 42°for 60 min, during cisplatin administration. The protocol advised six weekly cycles of combined treatment. Nineteen pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Cisplatin has emerged as the most active single agent for treating patients with metastatic disease, and no other standard cytotoxic drug has been consistently associated with objective response rates of ≥25%. However, for patients who experience relapse following definitive radiation therapy, cisplatin has only a minor effect ( 6 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cisplatin has emerged as the most active single agent for treating patients with metastatic disease, and no other standard cytotoxic drug has been consistently associated with objective response rates of ≥25%. However, for patients who experience relapse following definitive radiation therapy, cisplatin has only a minor effect ( 6 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…The recurrence rate is lower for patients with a pelvic recurrence within previously irradiated areas than for those with extra-pelvic sites of disease. In addition, the responsiveness of pelvic recurrences is partial at best and has a brief (median 4–6 months) duration ( 6 ). To enhance the therapeutic response, chemotherapy was combined with hyperthermia (cisplatin + hyperthermia for previously radiated cases), which has been demonstrated to be feasible ( 7 ) when used in tri-modal applications for the cervix ( 8 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that this form of trimodality treatment is feasible and effective with only moderate toxicity. Also, multiple studies in recurrent cervical cancer show that hyperthermia enhanced the uptake and cytotoxicity of cisplatin without additional side effects [ 19 , 179 181 ]. Summarizing, hyperthermia has shown very significant enhancement of the effectivity of both radiotherapy and chemotherapy without increasing toxicity in various multi-modality settings.…”
Section: Introductionmentioning
confidence: 99%
“…Two systematic reviews with meta-analysis 7,8 (reporting on seven RCTs), five publications on three RCTs, 19,20,28,29,33 and six singlearm trials were included. [34][35][36][37][38][39] The latest systematic review, which performed two separate analyses (conventional and network meta-analysis) of LRHT for Three controlled trials yielded five publications since the last systematic review. 19,20,28,29,33 One multicentre RCT (n = 101) that included treatment-naive patients with locally advanced cervical cancer reported that the addition of LRHT to CRT did not improve overall five-year survival (adjusted hazard ratio [HR]: 0.485, 95% CI: 0.217-1.082, p = 0.077), disease-free survival (DFS) (adjusted HR: 0.517, 95% CI: 0.251-1.065, p = 0.073), local relapse-free survival (LRFS) (p > 0.05) or CR (p > 0.05) compared with CRT alone.…”
Section: Cervical Cancermentioning
confidence: 99%